Improving Thai undergraduate students’ web design skills for smartphones through a collaborative blended learning approach - Pimdee, Paitoon; Wuttikamonchai, Oraboot; Sukkamart, Aukkapong; Meedee, Chontawat; Meekhobtong, Sirinthorn (Frontiers in Education, 2025)
PurposeThe increasing ubiquity of smartphones has created a growing demand for web designers skilled in creating responsive, user-centered, and smartphone-accessible websites. However, Thai undergraduate students often lack specialized training in mobile website design, highlighting a critical gap in digital education. While cooperative and blended learning has been recognized as effective pedagogical strategies, there is limited research on how these approaches can be integrated to address specific skill gaps in mobile web design. This study aims to develop and evaluate a Collaborative-Blended Learning Management Model (CBLMM) to enhance students’ proficiency in smartphone website design.MethodsThe CBLMM was developed by synthesizing cooperative and blended learning literature and a needs assessment focused on mobile web design competencies. The model consists of six key stages: (1) online self-study, (2) in-class lectures, (3) group activities, (4) project presentations, (5) summarization and evaluation, and (6) discussion and reflection. The model was evaluated by nine experts using a connoisseurship approach, assessing its usefulness, feasibility, appropriateness, accuracy, and effectiveness. To test the model’s efficacy, an experimental study was conducted with 19 third-year students enrolled in a web design course.ResultsExpert evaluations indicated that the CBLMM received high ratings across all assessment criteria. The experimental results showed a statistically significant improvement in students’ mobile website design skills, surpassing the 60% benchmark with significance at p < 0.05. Post-learning assessments also revealed marked improvements in user experience (UX) design compared to pre-learning performance. The effect size analysis indicated a moderate practical impact on skill development (d = 0.44) and a significant effect on academic achievement (d = 1.18).DiscussionThese findings suggest that structured, collaborative, and blended learning approaches can effectively equip students with essential digital design skills, filling critical gaps in higher education curricula. The study contributes to the field by demonstrating the CBLMM’s potential for enhancing mobile web design education, with broader implications for curriculum development and instructional design. Future research should explore the model’s applicability in diverse educational settings, examine long-term skill retention, and integrate emerging technologies such as AI-driven adaptive learning to refine digital education strategies further.